(untitled) (Research, Society and Development, 2021)
Introduction: Researchers at Rockefeller University, New York, found in some seriously ill patients with Covid-19 a type of autoantibody that attacks other cells of the immune system. For scientists, this would be an indication that these patients had preexisting autoantibodies to the disease and that this would be the reason why they developed the severe form of Covid-19. Objective: Answer what is the evidence on the infection by Sars-CoV-2 and triggering of autoimmunity. Methodology: This is a descriptive research of the integrative literature review type, which sought to answer what is the evidence on Sars-CoV-2 infection and triggering of autoimmunity. The search was carried out through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases Information Services, July 2021. Results: It is believed that Covid-19 has clinical characteristics similar to autoimmune diseases, as both share major immune responses of pathogenesis. Case reports of patients who developed Guillain-Barré syndrome, autoimmune hemolytic anemia and systemic lupus erythematosus were presented. Conclusion: Sars-CoV-2 can alter self-tolerance and generate autoimmune responses through cross-reactivity with host cells. However, it will be up to the scientific community to investigate this possibility further to validate or disprove this hypothesis, given the ease of detecting autoantibodies, thus corroborating the finding that they, triggered or not by Covid-19, are really a threat of alteration in the immune system.